Utilization of skipjack tuna Katsuwonus pelamis offal waste for mass culture of Daphnia sp. as feed for Betta sp. - Cahyono, Indra; Mutmainah, Sri Nurul; Basir, Buana; Mulyawan, Ardi Eko; Mulyani, Sri (Jurnal Akuakultur Indonesia, 2025)
This study aims to assess the impact of skipjack tuna (Katsuwonus pelamis) offal soaking water on the mass culture of Daphnia sp. for the growth of Betta fish (Betta sp.). This study was conducted for 30 days with treatment of offal 4.5 ml/L (treatment B), 7.5 ml/L (treatment C), 10.5 ml/L (treatment D) and commercial feed without skipjack offal soaking water as control (treatment A). The variables data of this study consisted of growth rate and population density of Daphnia sp., which were analyzed using variance analysis. The results showed that the highest population growth rate was found in the treatment of offal soaking water 4.5 ml/L with a value of 11.59% and a density of 260 individuals/liter on the 19th day of rearing. Daphnia sp. produced from soaking tuna offal can also be used as a natural food for the growth and development of Betta fish, although its effectiveness is still lower than other organic materials. Keywords: Daphnia sp., growth, mass culture, skipjack offal ABSTRAK Penelitian ini bertujuan untuk mengetahui pengaruh air rendaman jeroan ikan cakalang (Katsuwonus pelamis) pada kultur massal Daphnia sp. terhadap pertumbuhan ikan Betta (Betta sp.). Penelitian ini dilakukan selama 30 hari dengan perlakuan air rendaman jeroan ikan cakalang sebanyak 4,5 ml/L (perlakuan B), 7,5 ml/L (perlakuan C), 10,5 ml/L (perlakuan D) dan pakan komersil tanpa air rendaman jeroan ikan cakalang sebagai kontrol (perlakuan A). Data variabel penelitian terdiri dari laju pertumbuhan dan kepadatan populasi Daphnia sp. dianalisis menggunakan analisis ragam. Hasil penelitian menunjukkan bahwa laju pertumbuhan populasi tertinggi pada perlakuan menggunakan air rendaman jeroan 4,5 ml/L dengan nilai 11,59% dan dengan kepadatan individu 260 individu/liter pada hari pemeliharaan ke 19. Daphnia sp. yang dihasilkan dari perendaman jeroan ikan cakalang juga dapat digunakan sebagai pakan alami untuk pertumbuhan dan perkembangan ikan Betta (Betta sp.) walaupun efektivitasnya masih lebih rendah dibandingkan bahan organik lainnya. Kata kunci: Daphnia sp., jeroan cakalang, kultur massal, pertumbuhan